El movimiento doble: actores insiders y outsiders en la emergencia de una sociedad civil transnacional en las Américas. - William C. Smith.; Roberto Patricio Korzeniewicz. (Colombia Internacional, 2006)
The Summit process in the Americas and the complex negotiations around the FTAA are specific manifestations, at a regional level, of broader transformations in the international politics and the world-economy. But in a “double movement,” the global expansion of markets has simultaneously generated pressures that seek a social and political regulation of those markets. Thus, regional networks and coalitions and, in some cases, transnational social movements, have acquired the capacity to deploy, sometimes simultaneously and sometimes sequentially, strategies that range from collaboration and participation in existing institutional arrangements (strategy that we characterize as “insider”), to opposition and contestation of the central forces and logic of globalization (strategy that we characterize as “outsider”). We argue that the equilibrium between these two strategies has been recently altered by shifts in the structure of political opportunities in the region.